Penerapan Bisnis Komunitas Genarasi Z (Gen-Z) Berdasarkan Prinsip Ekonomi Syariah - Zadida Ugraha Kendy; Tia Wati; Dwiana Maharani; Rio Syahputra; Muhammad Syahlan Habibi; Wijiat Mia Ningrum (CV. Doki Course and Training, 2024)
ABSTRACT Economic activity will really refer to the extent to which economic actors understan Insight into economics and economic values ​​that are suitable for use in each Economic activity. One of which is the application of Islamic business amonggeneration Z, Business or Business is one of the priorities in developing the national economy and population The number of generation Z is 74.93 million or 27.94% of the total population of Indonesia (Central Statistics Agency, 2022). This research aims to find out the exten Business implementation among generation Z based on sharia economic views. Methodology Used in this research is a qualitative method to explore understandin In depth about generation Z who have made a major contribution to economic development. ABSTRAK Kegiatan ekonomi akan sangat mengacu pada sejauh mana para pelaku ekonomi memahami wawasan ekonomi dan nilai-nilai ekonomi yang cocok untuk digunakan dalam setiap kegiatan ekonomi. Salah satunya adalah penerapan bisnis syariah dikalangan generasi Z. Bisnis atau Usaha merupakan salah satu prioritas dalam membangun perekonomian nasional dan jumlah penduduk generasi Z sebanyak 74,93 juta atau 27,94% dari total jumlah penduduk Indonesia (Badan Pusat Statistik, 2022). Penelitian ini bertujuan untuk mengetahui implementasi bisnis di kalangan generasi Z berdasarkan pandangan ekonomi syariah. Metodologi yang digunakan dalam penelitian ini adalah metode kualitatif untuk menggali pemahaman secara mendalam mengenai generasi Z yang telah memberikan kontribusi besar dalam pembangunan ekonomi.